Sustainable and optimized power solution using hybrid energy system - Poorva Maggu; Sugandha Singh; Anurag Sinha; Cresantus N Biamba; Celestine Iwendi; Arshad Hashmi (Energy Exploration & Exploitation)
This research study aims to develop and implement a sustainable and effective power solution for metropolises with a power demand ranging from 2.5 to 25 MW. The primary objective is to create a hybrid energy system (HES) that integrates various power sources, such as fuel cells and solar photovoltaic (PV), with the existing utility grid, thereby satisfying energy needs while minimizing dependency on conventional fuel-based energy sources like coal and oil. To achieve this, a thorough examination of the energy demand, availability of renewable resources, and current power infrastructure is conducted. This examination focuses on optimizing the design of the HES by considering critical factors such as grid integration, power generation capacity, energy storage capacity, and control strategies. The feasibility and performance of the proposed HES are assessed using a combination of simulation tools, mathematical modeling, and system analysis methodologies. The study carefully evaluates key factors such as system efficiency, reliability, and cost-effectiveness to ensure a durable and economically viable solution. The abstract of this study emphasizes the main quantitative findings, such as a 25% decrease in energy costs and a 30% boost in overall system efficiency, positioning the HES as an attractive choice for sustainable energy management. In addition to the technical aspects, the paper examines the environmental impacts of the HES, particularly its contribution to reducing carbon emissions and promoting clean energy usage. The research seeks to enhance the sustainability and efficiency of the city's energy supply by reducing reliance on fossil fuels, paving the way for a transition to more resilient and sustainable energy solutions. The findings underscore the potential benefits of incorporating renewable energy resources into the existing system, which could lead to lower greenhouse gas emissions, increased energy independence, and improved energy security for the city or facility.